Implementasi Kurikulum Merdeka Belajar (KMB) pada Mata Pelajaran PPKn Kelas XI F1 di SMA Negeri 2 Sipora Kabupaten Kepulauan Mentawai - Sayidah, Sayidah; Jaenam, Jaenam; Juliardi, Budi (Asian Journal of Early Childhood and Elementary Education, 2023)
This research is motivated by problems, namely: How are the obstacles to implementing the independent learning curriculum (KMB) in PPKn class XI F1 subjects at SMA Negeri 2 Sipora. The purpose of this research is to describe the implementation of the independent learning curriculum in PPKn class XI F1 1 subjects at SMA Negeri 2 Sipora, What are the obstacles in implementing the independent learning curriculum in PPKn class XI F1 at SMA Negeri 2 Sipora. This type of research is descriptive qualitative research, namely research that provides an overview of factual and systematic situations and events regarding factors, characteristics, and relationships between phenomena that are owned to know the basics only, informants are school principals, curriculum representatives , student representatives, PPKn teachers, and students. Data collection techniques used are observation, interview, and documentation techniques. Data processing with data reduction, data presentation, and conclusion/verification. The results showed that: 1) Implementation of the independent curriculum (KMB) learning in PPKn class XI F1 at SMA Negeri 2 Sipora, Mentawai Islands Regency, namely the implementation of the independent learning curriculum focused more on students, 2) The obstacles faced were in public high schools 2 Sipora uses 2 curricula, namely the independent learning curriculum and K-13 and has been equipped with 3 driving teachers and there will be more prospective driving teachers at SMA Negeri 2 Sipora. Based on the results of the study it can be concluded that 1) Implementation of the independent learning curriculum in PPKn class XI F1 SMA Negeri 2 Sipora based on interviews with school principals, vice curricula, student vice teachers, PPKn teachers, and students, that the implementation of the independent learning curriculum in SMA Negeri 2 Sipora on PPKn subjects is more student-centered and gives freedom to students to develop the potential that each student has, of course, is different, where the independent curriculum curriculum is the teacher's freedom to choose material that is important to teach and the teacher too. free to use the media that will be used in learning, 2) Obstacles to the implementation of the independent learning curriculum in PPKn class XI F1 subjects at SMA Negeri 2 Sipora, the implementation of this independent learning curriculum must have planning starting from violations, procurement of educational facilities, training, mentoring and evaluation of success and failure, targets for SMA Negeri 2 Sipora for the next 1 year, 2 years, 3 years implementing the independent learning curriculum.